PENGARUH PELAKSANAAN PERENTING TERHADAP KOLABORASI ORANG TUA DENGAN GURU DALAM MENDAMPINGI ANAK MENJALANI PENDIDIKAN DI SMP IT RABBI RADHIYYA REJANG LEBONG - Pandy Akbar Wirawan; Hartini; Muhammad Istan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of parenting program implementation on collaboration between parents and teachers when assisting students' education at Rabbi Radhiyya IT Junior High School, Rejang Lebong. Using a quantitative approach with a survey method, data was obtained through a questionnaire involving a sample of students in grades VII, VIII, and IX. Data analysis was done using SPSS version 25. The results showed that the implementation of the parenting program had a significant effect on parent-teacher collaboration, with the level of influence classified as moderate (16%). Good implementation of parenting can improve communication and parental involvement in supporting children's education, as well as creating synergy between home and school. However, challenges such as time constraints and varying levels of parental participation are still obstacles to optimizing the program. This study concludes that the implementation of a structured, relevant and inclusive parenting program is essential to improve collaboration between parents and schools. Continuous evaluation is also needed to ensure the effectiveness of the program in supporting students' academic achievement and character development.